2021
DOI: 10.29130/dubited.737211
|View full text |Cite
|
Sign up to set email alerts
|

Saldırı Tespit Sistemi İçin İstifleme Topluluk Öğrenme Yaklaşımı

Abstract: Intrusion detection systems (IDSs) have received great interest in computer science, along with increased network productivity and security threats. The purpose of this study is to determine whether the incoming network traffic is normal or an attack based on 41 features in the NSL-KDD dataset. In this paper, the performance of a stacking technique for network intrusion detection was analysed. Stacking technique is an ensemble approach which is used for combining various classification methods to produce a pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…The algorithms used are Decision Tree (DT), K Nearest Neighbor (KNN), Neural Network and Logistic Regression (LR) which are considered as base learner models and Support Vector Machine (SVM) which are considered as meta learner. Through the results, it is shown that stacking helps to improve the performance of intrusion detection systems, as the proposed DT-LR-ANN + SVM model achieved an accuracy of 84.32% (Ucar et al, 2021(Ucar et al, :1331(Ucar et al, -1336.…”
Section: Related Workmentioning
confidence: 99%
“…The algorithms used are Decision Tree (DT), K Nearest Neighbor (KNN), Neural Network and Logistic Regression (LR) which are considered as base learner models and Support Vector Machine (SVM) which are considered as meta learner. Through the results, it is shown that stacking helps to improve the performance of intrusion detection systems, as the proposed DT-LR-ANN + SVM model achieved an accuracy of 84.32% (Ucar et al, 2021(Ucar et al, :1331(Ucar et al, -1336.…”
Section: Related Workmentioning
confidence: 99%
“…For an optimal classification result, UÇAR et al (13) they tested several algorithms as base predictors and the SVM model is used as meta-estimator for the different stacked models, the 4 stacked models are tested with NSLKDDTest+ and NSLKDDTest 21 data, the best prediction rate is scored for the model based on DT,ANN, LR as base predictors and SVM as meta-estimator, they achieved 90 % in the best case.…”
Section: Previous Work Of Machine Learning Applications In Intrusion ...mentioning
confidence: 99%